Optimization of Emergency Response to Earthquake Disasters for High School Students Related to Evacuation and Transportation of Disaster Victims - Pamungkas, Indra Gilang; Palupi, Eva Riantika Ratna; Suprayogi, Suprayogi; Khoirot, Risyda Ma'rifatul; Zaharany, Tsania Ayu; Risdianti, Helza; Firstania, Aurellia; Agustian, Irwan; Nugroho, Kristianto Dwi; Hanafiah, Yusuf (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Earthquakes are natural disasters that frequently occur and cause serious impacts, including physical destruction and injuries among victims. Data indicate that the incidence of earthquakes, particularly in Indonesia, continues to rise each year, thereby requiring rapid and appropriate management through effective evacuation and victim transportation. However, public knowledge, especially among students, remains low, highlighting the need for educational programs to improve their ability to conduct evacuation and transportation during earthquake disasters. This community service activity was carried out to enhance students’ skills in performing evacuation and transportation of earthquake victims. This community service was carried out using the CERDAS method (Lecture, Demonstration, and Simulation), involving 4 groups consisting of 16 participants. The evaluation was conducted using a skills checklist during simulation. The results showed the percentage of achievement relative to the maximum score in each group, with 84.09% in group 1, 86.36% in group 2, 90.90% in group 3, and 86.36% in group 4. The SMART method can be used to improve aid and transportation for earthquake victims. This needs to be done routinely to improve students' evacuation and transportation skills. Keywords: Disaster Emergency Response, Earthquake, Evacuation and Transportation